Pemberian Izin Peredaran Minuman Beralkohol Berdasarkan Peraturan Gubernur Bali Nomor 1 Tahun 2020 - I Nyoman Sadhu Bramanta; Ida Ayu Putu Widiati; Luh Putu Suryani (Jurnal Preferensi Hukum, 2020)
There are various kinds of businesses or activities in the field of trade, one of which is a trade or distribution of alcoholic drinks. Based on the Regulation of the Minister of Trade of the Republic of Indonesia Number 20 / M-DAG / PER / 4/2014 Article 18 Paragraph (1) that every company that trades alcoholic drinks is required to have SIUP-MB. Alcoholic drinks can only be traded by companies that already have a business license for alcoholic drinks in accordance with their classification. This research is important to be carried out with the aim to find out the mechanism for granting alcoholic beverage distribution license based on Bali Governor's Regulation No. 1 of 2020 and the implications of Bali's Governor's Regulation No. 1 of 2020 to alcoholic beverage trade businesses. This research is a normative legal research, namely by using the statutory approach. The mechanism for granting licenses for the distribution of alcoholic drinks based on Bali Governor Regulation No. 1 of 2020 is that business operators must follow procedures and fulfill certain requirements in applying for SIUP-MB, then submit a permit application to the Provincial Trade and Industry Office, after the issuance of a business by the Trade and Industry Office , then the business actor can carry out the desired trading business. Implications of Bali Governor Regulation Number 1 of 2020 Regarding the management of fermented drinks and/or distinctive distinctive Bali for the business of the alcoholic beverage trade, the benefits are felt, the crafters or farmers of fermented drinks and/or distinctive distinctive Bali have legal certainty and certainty of trying to do fermented and distillation drinks production activities typical of Bali.